Successful Resection of Isolated Para-Aortic Lymph Node Recurrence from Advanced Sigmoid Colon Cancer following 156 Courses of FOLFIRI Regimen - Kaoru Takeshima; Kazuo Yamafuji; Atsunori Asami; Hideo Baba; Nobuhiko Okamoto; Hidena Takahashi; Chisato Takagi; Kiyoshi Kubochi (Case Reports in Surgery)
Isolated para-aortic lymph node (PLN) recurrence from colorectal cancer (CRC) is rare, with no currently validated treatments. Few reports have described the successful resection of isolated PLN involvement from CRC following chemotherapy. We report the case of a 63-year-old man who underwent sigmoidectomy for sigmoid colon cancer at our hospital. Pathological examination demonstrated advanced sigmoid colon cancer with metastatic involvement in both of the tested PLNs. Palliative chemotherapy was initiated four weeks after surgical resection, with administration of the FOLFIRI regimen. Four years after the operation, computed tomography (CT) revealed an enlarged PLN below the left renal vein. As PLN enlarged to 15 mm in the minor axis on a CT scan in 2014 after receiving a total of 156 courses of the FOLFIRI regimen, we considered the enlarged PLN to represent an isolated metastasis. Accordingly, lymph node resection was performed with microscopically negative margins. The patient maintained a good quality of life without any side effects throughout the whole course of his treatment and remains disease-free at 24 months without chemotherapy after resection of the isolated PLN. Curative resection following chemotherapy may improve survival of carefully selected advanced CRC patients with locoregional recurrence, such as isolated PLN involvement.